DETERMINATION OF NON-SPECIFIC AND SPECIFIC QUALITY PARAMETERS OF MARIGOLD SIMPLICIA AS A RAW MATERIAL FOR MEDICINAL PREPARATIONS - Martina; Samsuri; I Made Merdana; I Wayan Sudira; Putu Devi Jayanti (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
Marigold flower (Tagetes erecta L.) is a type of ornamental plant from the Asteraceae family that has significant potential for cultivation due to its numerous uses. Besides being an ornamental flower, a natural dye, and an attractant for pest predators, marigold contains carotenoids, which can act as antioxidants, relieve mild fever and sore throat, serve as a natural moisturizer, and function as a natural mosquito repellent. Given its various beneficial components and properties, marigold has the potential to be used as a raw material for pharmaceutical preparations. This study aims to determine whether marigold flower simplicia meets the requirements as a raw material for pharmaceutical preparations based on non-specific and specific parameters according to established standards. The non-specific parameters include moisture content and ash content tests, while the specific parameters include organoleptic tests, water-soluble extract content, ethanol-soluble extract content, and yield percentage. This research is an observational non-experimental study with a descriptive-qualitative analysis design. Data collection was carried out by conducting non-specific and specific tests to obtain results for each parameter. The obtained results were as follows: moisture content 4.95%, ash content 4.8%, water-soluble extract content 37.34%, ethanol-soluble extract content 28%, and yield 13.48%. Based on these results, it can be concluded that the marigold flower simplicia is suitable and meets the requirements to be used as raw material for medicinal preparations, in accordance with the previously established parameters, namely the Materia Medica Indonesia Volume VI of 1995, the Ministry of Health of the Republic of Indonesia in 2017, and the Regulation of the Head of the Indonesian Food and Drug Authority (BPOM) Number 32 of 2019 concerning the quality requirements for traditional medicines. Further quality standardization tests should be conducted, such as microbial contamination, total aflatoxin, heavy metal contamination, weight uniformity, and alcohol content determination in marigold flower simplicia to establish additional quality standards across different parameters.